ANTIBACTERIAL ACTIVITY ETHYL ACETATE EXTRACTS OF EARTHWORMS (Lumbricus rubellus, Eisenia foetida, Nereis sp) TOWARD Staphylococcus aureus, Enterococcus faecalis, Salmonella thyposa INVITRO - Kartikaningsih, Hartati; Maharani, Sarastria; Sartika, Fitarina (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2019)
Earthworms had a mechanism of antibacterial. The research aimed to observe Lumbricus rubellus, Eisenia foetida, Nereis sp. antibacterial activity against Salmonella thyposa, Staphylococcus aureus, Enterococcus faecalis in vitro compared to ampicillin antibiotics. All the worms extracted using ethyl acetate extraction and tested their MIC. The compound of amino acids of the worms was analyzed by HPLC and nanodrop. Lumbricus rubellus was the best anti-bacteria activity followed by Eisenia foetida and Nereis sp., but these activities less than ampicillin antibiotic. Observations with SEM showed these worms extract caused cell leakage in all of these bacteria. Protein content with Nanodrop testing revealed the highest protein content was Lumbricus rubellus (21.75 ppm) followed by Eisenia foetida (21.32 ppm) and Nereis sp. (20.98 ppm), as well as for amino acids levels, there were Lumbricus rubellus (24.66%), Eisenia foetida (22.78%), Nereis sp. (18.37%). From the 15 amino acids detected, all of the worms had the same sequence of fourth the highest amino acids (Glutamate, Aspartate, Leucine, Arginine) and fourth the lowest amino acid levels (Methionine, Hystidin, Tyrosin, Glisan). It had not been tested amino acid sequences of antibacterial compounds of these worms (Lumbricin 1: Phe-Ser-Lys-Tyr-Glu-Arg in Lumbricus rubellus worms, Fetidin 1: Ala-Met-Val-Ser-Ser and Fetidin 2: Ala-Met- Val-Gly-Thr in the Eisenia foetida worm, Hemerythrin: His-Glu-Asp in Nereis sp).